TAKAYASU ARTERITIS IN CHILDREN - Safia Al Abrawi; Marine Fouillet-Desjonqueres; Louis David; Xavier Barral; Pierre Cochat; Rolando Cimaz (Amaltea Medical Publishing House, 2009)
Takayasu arteritis (TA) is a large vessel vasculitis that usually affects young female patients during the second and third decades of life, but has been reported in children as young as 24 months of age. Aim of this report was to describe four children (two girls) with TA, as well as summarizing main published studies. The mean age at presentation of our cases was 11 years (range 8-15). Three patients were Caucasians and one Asian. Arterial hypertension was the commonest mode of presentation followed by systemic symptoms. Other related symptoms were due to ischemia and consisted of abdomen, chest, and limb pain. An abdominal bruit was noted in only one patient. Inflammation markers were always abnormal. Angiography was performed in all cases; left subclavian artery and common carotid artery were more frequently involved. Renal artery stenosis was observed in two patients. One boy was diagnosed as having an associated immune deficiency (WiskottAldrich syndrome). Treatment modalities included prednisone (n = 4), methotrexate (n = 3), and mycophenolate mofetil (MMF) (n = 1). Surgery was required in two patients. Follow-up ranged from 3 to 10 years since diagnosis. In three cases antihypertensive drugs and methotrexate were stopped, and prednisone was reduced to 7.5 mg/day.